COMPARISON ANALYSIS OF LOCAL GOVERNMENT FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC AND ITS IMPACT ON ECONOMIC GROWTH - Nuwun Priyono; Risma Wira Bharata; Whinarko Juli Prijanto (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to analyze the differences in the ratios of financial independence, financial flexibility, operational solvency, short-term solvency, long-term solvency, and regional service solvency in the Provinces of Central Java and D.I. Yogyakarta before and during the Covid-19 Pandemic and its impact on economic growth. The samples were districts and cities in Central Java Province and D.I. Yogyakarta. The data used is secondary data taken from the directorate general of financial balance of the Indonesian Ministry of Finance. The sampling technique used is purposive sampling. The analytical tool used in this study is the Difference Test. The results showed that of the 6 financial performance indicators, 4 indicators did not show a significant difference and 2 indicators showed a significant difference between the pre-pandemic period and during the Covid-19 pandemic period. Then, economic growth experienced a significant difference between the pre-pandemic period and during the Covid-19 pandemic.